2005
DOI: 10.1038/oby.2005.191
|View full text |Cite
|
Sign up to set email alerts
|

PIXImus DXA with Different Software Needs Individual Calibration to Accurately Predict Fat Mass

Abstract: Research Methods and Procedures: C57BL/6J (n ϭ 16) and Aston (n ϭ 14) mice (including ob/ob), Siberian hamsters (Phodopus sungorus) (n ϭ 15), and bank voles (Clethrionomys glareolus) (n ϭ 37) were DXA scanned postmortem, dried, then fat extracted using a Soxhlet apparatus. We compared extracted FM with DXA-predicted FM corrected using an equation designed using wild-type animals from split-sample validation and multiple regression and two previously published equations. Sixteen animals were scanned on both a G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 14 publications
3
33
0
Order By: Relevance
“…Animals receiving the restricted diet lost on an average 1.3G0.32 g (K5.5%) of BM, which was attributed to a decrease in LM while FM increased (figure 2). Large errors in small animal DXA estimates of FM have been shown for animals with less than 5 g of fat ( Johnston et al 2005) and since LM is calculated by subtraction of FM from total tissue mass, both LM and FM for restricted animals may be incorrect. This may also explain why FM of restricted animals was not different from controls post-treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Animals receiving the restricted diet lost on an average 1.3G0.32 g (K5.5%) of BM, which was attributed to a decrease in LM while FM increased (figure 2). Large errors in small animal DXA estimates of FM have been shown for animals with less than 5 g of fat ( Johnston et al 2005) and since LM is calculated by subtraction of FM from total tissue mass, both LM and FM for restricted animals may be incorrect. This may also explain why FM of restricted animals was not different from controls post-treatment.…”
Section: Resultsmentioning
confidence: 99%
“…There are some controversies regarding the accuracy of measuring fat mass between DEXA scan and chemical extraction (carcass analysis). Johnston et al (17) found that DEXA scan underestimated fatty mass for obese animals and overestimated fatty mass for lean animals. However, other authors found that DEXA scan overestimated fat mass content in lean and obese mice (3,26).…”
Section: Discussionmentioning
confidence: 99%
“…The software enabled a region of interest to be created to exclude the head with the mask from analysis [15]. Data were corrected with a calibration formula specific to our machine that has been generated by the linear regression of fat content determined by DXA analysis, with the fat content as determined by soxhlet chemical extraction (see [25] for detailed description of the procedure).…”
Section: Body Compositionmentioning
confidence: 99%